Therapeutic and protective effect of oxymetholone against mortality induced by gamma irradiation in mice - Hosseinimehr, Seyed Jalal; Zakaryaee, Valiallah; Froughizadeh, Mohsen (Archives of Medical Science, 2009)
Introduction: Oxymetholone can stimulate bone marrow cells and increase the blood cells in the peripheral blood vessels. Previously we showed that administration of oxymetholone as a single dose increased survival rate in mice against a lethal dose of γ irradiation. In this study, we determined the percentage survival rate in irradiated mice treated with oxymetholone at divided low dose and prior and after irradiation. Material and methods: Oxymetholone at different doses (40, 80, 160 and 320 mg/kg) was administered to mice by gavage with starting time at 24 h before or 1 h after exposure to a lethal dose of γ irradiation for four consecutive days. Mortality was recorded daily for 30 days. The percentage survival rates were compared with two-sample test for proportions. Results: At 30 days after treatment, the percentage of animal survival in each group was between 15 and 25%, compared to 0% in control-irradiated mice. Administration of oxymetholone at a single dose of 640 mg/kg increased survival rate to 40%. Oxymetholone treatment increased survival rate in mice when administered after irradiation at divided low doses. Conclusions: Oxymetholone had potential effects on increasing survival rate when administered after γ irradiation in mice at divided low doses. With the therapeutic effects of oxymetholone, it can be used for reducing mortality induced by γ irradiation after exposure to irradiation.